Comparison of axial behavior of RC columns using alkali-activated slag-based concrete and OPC concrete during and after fire - Liu, Yuzhong (2023)
As no study on fire behavior of RC columns using alkali-activated concrete has been reported so far, this paper presents an experimental program comparatively investigating the thermal response and structural behavior of reinforced columns using alkali-activated slag-based concrete (AAC) and Portland cement-based concrete (PCC) during and after subjecting to the standard fire curve, with concrete strength and fire duration as test parameters. The experimental and analytical studies showed that compared with PCC columns, AAC columns had slightly lower temperature field but faster increase of axial deformation during fire. AAC and PCC columns using normal-strength concrete had equivalent residual axial capacity after exposure to fire. However, AAC columns using high-strength concrete retained greater load-bearing capacity than their PCC counterparts due to the spalling of high-strength PCC columns. AAC columns had lower axial stiffness than PCC columns at ambient temperature due to lower elastic modulus of AAC, but they had similar axial stiffness after exposure to fire of 2 h since PCC underwent more degradation of elastic modulus under high temperature. Furthermore, as concrete strength and fire duration increased, the axial contraction under heating and axial capacity loss after heating of AAC columns increased. A numerical method based on finite difference was used to predict the temperature field and corresponding residual axial capacity of RC columns after the fire.